Effectiveness of Crowberry on Plasma Total Antioxidant Status, Lipid Profile and Homocysteine (Science and Education Publishing, 2013)
The objective of this study was to assess whether the consumption of crowberry could affect serum lipid profile, homocysteine (Hcy) level, and antioxidant status of healthy subjects. Out of 55 healthy volunteered subjects, 51 completed this investigation to final analysis. Each subject consumed 2 grams of powdered crowberries everyday for four weeks. Crowberry consumption led to significant increase in total antioxidant status (TAS) and superoxide dismutase (SOD), while it resulted in significant decrease in total cholesterol and low-density lipoprotein (LDL) levels. The differences in the levels of antioxidant markers and lipid profiles taken before and after crowberry intake were most significant. The levels of Hcy, catalase, T-cho, triglyceride, and LDL in the higher T-cho group decreased significantly after crowberry intake. Furthermore, this study revealed a significant positive correlation between Hcy level and body weight index (BMI). Crowberry intake improved lipid profile as demonstrated by having decreased T-cho, TG and LDL; increased antioxidative reactions (such as TAS or SOD enzymatic activities) and decreased Hcy levels in healthy subjects.